1979
DOI: 10.1149/1.2129138
|View full text |Cite
|
Sign up to set email alerts
|

Impedance Measurements during Anodization of Aluminum

Abstract: The impedance of a growing anodic oxide layer is inductive in a rcertain frequency range. This effect is related to the occurrence of transients after changes in current density or applied electric field. Measurements on aluminum samples in the frequency range 5 mHz-10 kHz and the current density range 3 X 10-6-5 • ]~O -3 A/cm 2 and in various electrolytes are presented and compared with a theory in which the relaxation effect is ascribed to a buildup of surface charge at the metal-oxide interface.It has long … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
0
1

Year Published

1979
1979
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(32 citation statements)
references
References 16 publications
5
26
0
1
Order By: Relevance
“…Figure shows two examples of the electrochemical impedance response of the iron electrode in 1 M H 3 PO 4 solution on the passive domain for two different potentials. The shape of these diagrams is similar to results obtained for passive iron in H 2 SO 4 solution but also on different metals such as W, Al, Mo, or Nb, on which much thicker, 3‐D, anodic oxide films are grown. Quantitatively, the impedance response of diagrams presented in Figure shows three time‐constants and only slightly differs in magnitude as a function of the polarisation potential.…”
Section: Resultssupporting
confidence: 80%
“…Figure shows two examples of the electrochemical impedance response of the iron electrode in 1 M H 3 PO 4 solution on the passive domain for two different potentials. The shape of these diagrams is similar to results obtained for passive iron in H 2 SO 4 solution but also on different metals such as W, Al, Mo, or Nb, on which much thicker, 3‐D, anodic oxide films are grown. Quantitatively, the impedance response of diagrams presented in Figure shows three time‐constants and only slightly differs in magnitude as a function of the polarisation potential.…”
Section: Resultssupporting
confidence: 80%
“…After a survey of the electrochemical studies on the passivation of metals reported in literature, it was noticed that an interesting EIS behavior, as shown schematically in Figure a in the Nyquist representation, is very characteristic for the oxide films anodically growing on valve metals within the passive potential region in various electrolyte solutions (especially in aggressive solutions). This similar-shaped EIS spectrum was early measured by De Wit et al for anodized Al, Kelly for passivated Ti, and Keddam and co-workers , for passivated Fe. And now, it is so common for (and only limited to) the valve metals that it has been observed on most valve metals, such as Ti, , W, Nb, ,,, Mo, ,, Al, , Fe, ,, Ta, , and Bi …”
Section: Introductionsupporting
confidence: 81%
“…This similar-shaped EIS spectrum was early measured by De Wit et al for anodized Al, Kelly for passivated Ti, and Keddam and co-workers , for passivated Fe. And now, it is so common for (and only limited to) the valve metals that it has been observed on most valve metals, such as Ti, , W, Nb, ,,, Mo, ,, Al, , Fe, ,, Ta, , and Bi …”
Section: Introductionsupporting
confidence: 81%
“…3 i 4, dok su vrednosti parametara kola dati u tabeli 1. Korišćena EEK se često sreću u literaturi [13,17,[23][24][25][26], a induktivni element je uključen u EEK na sl. 3a i c. U svim EEK električna svojstva pasivnog filma predstavljena su elementima CPE p i R dl u paralelnoj vezi, odnosno elementom sa konstantnim faznim pomerajem koji se odnosi na kapacitivnost filma (parametar n u svim slučajevima ima vrednosti u opsegu 0,84-0,92, tabela 1) i otpornošću u porama filma, redom.…”
Section: Parametri Ekvivalentnih Električnih Kolaunclassified